Validitas Kurikuler Soal Tes EBTANAS Sekolah Dasar dan Menengah - Wachidi Wachidi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Curricular Validity of the Test Items for the Elementary School and Secondary School Ebtanas. This study was carried out to know if the test items in the Ebtanas fulfilled curricular validity. Data were collected by documentary study from the Bahasa Indonesia test items administered in the elementary school, junior high school and senior high school Ebtanas since 1985/1986. The data were analyzed by percentages. It was found out that, in terms of items relevance to the curricular objectives and material representativeness in each topic, the test items did not fulfill curricular validity.